Prevalence and associating factors for iatrogenic gliosis-like changes in surgically treated intracranial meningioma patients—A retrospective study of 255 meningioma patients - Joonas Laajava; Mika Niemelä; Miikka Korja (PLoS ONE, 2025)
Purpose Persistent peritumoral brain edema (PTBE) following surgery of intracranial meningioma (IM) has recently been proposed to represent, in part, iatrogenic gliosis-like changes (IGCs). We aimed to estimate the frequency of IGCs after gross total resection (GTR) of IM, identify factors associated with IGCs, and assess their effect on surgical outcome. Methods Patients with IM who underwent surgery between 2000 and 2020, presented with no preoperative PTBE on magnetic resonance imaging, and had at least one year of follow-up were retrospectively identified. Only patients without preoperative PTBE were included to ensure that postoperative hyperintense fluid-attenuated inversion recovery (FLAIR) changes were iatrogenic. Outcomes were evaluated based on postoperative symptoms and changes in Karnofsky Performance Status (KPS). Results A total of 255 meningioma patients without preoperative PTBE were identified. Of these, 133 (52.2%) showed postoperative IGCs on FLAIR imaging. IM location (p < .001), volume (p < .001) and World Health Organization grade (p = .003) associated with IGCs in univariate analysis. In multivariate analysis, non-convexity location (OR 2.0–12.2, p = .04 to <.001) and IM volume (OR 1.1, p < .001) remained significant. Patients with IGCs showed a modest KPS improvement from 86.7 to 88.0 (+1.3), while those without IGCs improved more from 90.0 to 92.5 (+2.5, p = .002). IGCs were associated with residual symptoms (OR 2.3, p = .01) and new-onset seizures (OR 6.1, p = .04). Conclusion IGCs are frequent following GTR of IM, and associate with IM location and volume. IGCs likely associate with impaired recovery following surgery and new-onset seizures.